Enhancement of immune response to a DNA vaccine against Mycobacterium tuberculosis Ag85B by incorporation of an autophagy inducing system - Meerak J. (2014)
DNA vaccines are a promising new generation of vaccines that can elicit an immune response using DNA encoding the antigen of interest. The efficacy of these vaccines, however, still needs to be improved. In this study, we investigated the effect of autophagy on increasing the efficacy of a candidate DNA vaccine against Mycobacterium tuberculosis (MTB), a causative agent of tuberculosis. Low molecular weight chitosan was used to encapsulate plasmid DNA containing a gene encoding MTB Antigen 85B (Ag85B), a secreted fibronectin-binding protein. To induce autophagy upon DNA vaccination, the kinase defective mTOR (mTOR-KD) was transfected into cells, and autophagy was detected based on the presence of LC3II. To investigate whether autophagy enhances an immune response upon DNA vaccination, we coencapsualted the Ag85B-containing plasmid with a plasmid encoding mTOR-KD. Plasmids encapsulated by chitosan particles were used for primary subcutaneous immunization and for intranasal boost in mice. After the boost vaccination, sera from the mice were measured for humoral immune response. The DNA vaccine with the autophagy-inducing construct elicited significantly higher Ag85B-specific antibody levels than the control group treated with the Ag85B plasmid alone or with the Ag85B plasmid plus the wild type mTOR construct. Upon in vitro stimulation of splenocytes from mice immunized with recombinant Ag85B, the highest levels of secreted IFN-γ and IL-2 were detected in mice immunized with the autophagy-inducing plasmid, while no differences in IL-4 levels were detected between the groups, suggesting that the DNA vaccine regimen with autophagy induction induced primarily a Th1 immune response. Furthermore, the enhanced proliferation of CD4+ T cells from mice receiving the autophagy-inducing vaccine was observed in vitro. Based on the evidence presented, we conclude that incorporating an autophagy-inducing element into a DNA vaccine may help to improve immune response. © 2012 Elsevier Ltd.